Internet of Things and Personalized Healthcare Systems - Krishna, P. Venkata; Gurumoorthy, Sasikumar; Obaidat, Mohammad S. (SpringerBriefs in Forensic and Medical Bioinformatics, 2019)
This book highlights the issues and challenges in personalised healthcare systems. The individual chapters address different aspects of such systems, including the novel Internet of Things (IoT) system architectures in healthcare and emerging e-health based IoT applications. Moreover, the book investigates the impact of cutting-edge innovations on the IoT.